Understanding the Association Between Spontaneous Quit Attempts and Improved Smoking Cessation Success Rates: A Population Survey in England With 6-Month Follow-up - Garnett, Claire (Nicotine Tob Res, 2019)
INTRODUCTION: Almost half of smoking quit attempts are “spontaneous” (initiated as soon as the decision to quit has been made) and are associated with increased success rates. This study aimed to assess to what extent other factors may account for this association. METHODS: Data were used from respondents to a survey representative of the adult population in England from 2006 to 2016. We included 2018 respondents who were current smokers at baseline and had attempted to quit between baseline and 6-month follow-up. Logistic regression models assessed the association between quit success and spontaneous quit attempts while adjusting for smoking, sociodemographic, and quit attempt characteristics. RESULTS: Spontaneous quit attempts were associated with greater odds of quit success (OR = 1.31, 95% CI = 1.07 to 1.60) but the association was not significant in the fully adjusted model (OR(adj) = 1.19, 95% CI = 0.95 to 1.49). In this adjusted model, those who attempted to quit without cutting down first (OR(adj) = 3.08, 95% CI = 2.46 to 3.88) and were male (OR(adj) = 1.44, 95% CI = 1.16 to 1.80) had greater odds of success; although a greater number of attempts in the past 6 months, stronger urges to smoke (strong vs. none), higher daily cigarette consumption, and lower social grade (E vs. AB) were associated with lower odds of success (OR(adj) range = 0.32–0.98, p < .030). Quit attempts made without cutting down first were correlated with spontaneous quit attempts (r = .150, p < .001) and appeared to account for the diminished association between spontaneous quitting and success (OR(adj) = 1.18, 95% CI = 0.96 to 1.46). CONCLUSIONS: The increased success rate of spontaneous quit attempts appears to be because spontaneous quit attempts are more likely to be made without cutting down first. IMPLICATIONS: The apparent benefit of spontaneous over planned quit attempts may be attributable to the former being more likely to involve quitting without cutting down first (ie, abrupt cessation) than cutting down first (ie, gradual cessation) and so this may be a more useful target for advice to improve the chances of successful quitting.